Electronic and optical properties of W–Sn-Z and W′-Sn-W′ monolayers using density functional theory. (November 2020) - Barhoumi, M.; Sfina, N.; Lazaar, K.; Said, M.
Abstract: Similar to graphene, the subject of stanene has stolen significant recognition both in experimental and theoretical areas. Nevertheless, stanene is poor when put into practice because it has zero band-gap energy, therefore it is necessary to use a universal strategy to achieve a material with a large band-gap. Employing density functional theory, we study the structural, electronic, and optical properties such as dielectric function and absorption coefficient of stanene monolayer functionalized with chemical groups, i.e., W–Sn-Z, Cl–Sn–Br, and W′-Sn-W′ (where W = Cl, F, or OH; Z = CN; and W′ = CN, CH, or NH). Our calculations reveal that the band-gap energy at the high symmetry points tuned in a range of 1.019–1.751 eV, which is significantly higher than the stanene monolayer with hydrogenation (0.3 eV). Furthermore, we found that under an external electric field the electronic band structures of various compounds are changed down in energy producing in a semiconductor to metal transition. Furthermore, we have computed other properties like the absorption coefficient, the refractive index, and the conductivity of our systems. Graphical abstract: Image 1 Highlights: We use a universal strategy to obtain a stable material with a large bandgap. The bandgap can be tuned in a large range of 1.019–1.751 eV. Functionalized stanene can be a semiconductor or even exhibit metallic properties. Applying an external electric field is another strategy to tune the band structure of the stanene monolayer functionalized.